Jensen – Ostrowski inequalities and integration schemes via the Darboux expansion - Cerone, P.; Dragomir, S. S.; Kikianty, E. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
By using the Darboux formula obtained as a generalization of the Taylor formula, we deduce some Jensen – Ostrowski-type inequalities. The applications to quadrature rules and f -divergence measures (specifically, for higher-order χ -divergence) are also given.